A generalized thermoelastic diffusion problem of thin plate heated by the ultrashort laser pulses with memory-dependent and spatial nonlocal effect. Issue 3 (5th January 2021) - Li, Yan; He, Tianhu; Luo, Pengfei; Tian, Xiaogeng
Abstract: Due to the advantages of high-power density, short duration, and high machining accuracy, ultrashort laser pulses are widely used in the fields of ultra-precision machining and microelectronic manufacture. In the manuscript, the L-S generalized thermoelastic diffusion theory considering the memory-dependent effect and spatial nonlocal effect is established and the thermoelastic diffusion responses of a semi-infinite thin plate subjected to a non-Gaussian laser pulse and a chemical shock on its boundary are studied. The Laplace integral transformation and its numerical inversion are used to solve the problem. The variation of the temperature, chemical potential, displacement, stress, and concentration with different nonlocal parameters, time delay factors, and kernel functions are obtained. The results show that heat conduction has a significant effect on mass transfer, while mass transfer has little effect on heat conduction; nonlocal parameter has a significant influence on displacement and stress, but little effect on temperature, chemical potential, and concentration. The establishment of this theory and the solution of the corresponding problem are aimed at reasonably predicting the transient responses of heat conduction and mass transfer under the coupling effects of mechanics, heat, and diffusion.